2013
DOI: 10.1007/s12264-013-1339-6
|View full text |Cite
|
Sign up to set email alerts
|

Feature-reduction and semi-simulated data in functional connectivity-based cortical parcellation

Abstract: Recently, resting-state functional magnetic resonance imaging has been used to parcellate the brain into functionally distinct regions based on the information available in functional connectivity maps. However, brain voxels are not independent units and adjacent voxels are always highly correlated, so functional connectivity maps contain redundant information, which not only impairs the computational efficiency during clustering, but also reduces the accuracy of clustering results. The aim of this study was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The results indicate that the combination of the K-means clustering algorithm and the FC can identify the functional networks of the human brain. The K-means algorithm has been commonly used to parcellate cortical or subcortical regions based on the static FC [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. These previous studies along with the present study extend the application of machine learning methods in brain sciences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicate that the combination of the K-means clustering algorithm and the FC can identify the functional networks of the human brain. The K-means algorithm has been commonly used to parcellate cortical or subcortical regions based on the static FC [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. These previous studies along with the present study extend the application of machine learning methods in brain sciences.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…The K-means clustering algorithm is one of the unsupervised learning algorithms [ 29 ]. Since the K-means clustering algorithm can cluster different observations into different clusters in a simple and easy way, it has been widely used in fMRI studies [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. For instance, Fan et al used the K-means clustering algorithm to parcellate the thalamus based on the static FC and found that the thalamus could be divided into seven symmetric thalamic clusters [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…PCA, as one of the simplest and robust ways to analyze multidimensional data, is a powerful statistical framework for the analysis of tractography-based parcellation (Thiebaut de Schotten et al, 2014;Cerliani et al, 2017) and has become increasingly popular recently in different studies (Markiewicz et al, 2011;Craddock et al, 2012;Leonardi et al, 2013;Tian et al, 2013;Nayal et al, 2014;Smith et al, 2018). Based on the theory of DWI and tractography techniques, the wholebrain connectivity of each voxel is deemed as multivariate dataset in the process of individual brain parcellation.…”
Section: Principal Component Analysismentioning
confidence: 99%
“…The prerequisite of this strategy is to define the sizes of functional regions. In general, one way to approach this problem is to refer to anatomical brain atlases or predefined brain parcellations, but these are either inaccurate or inconsistent ( 23 26 ). Moreover, there is no consensus on how many functional regions the brain contains.…”
Section: Introductionmentioning
confidence: 99%